Analysing the reality and importance of issuing Islamic sukuk in Malaysia - B. Djaouida; K. Chafia (Вестник университета)
The present study aims to shed light on the reality of the issuance of Islamic sukuk in Malaysia, which occupies the forefront in this field. This is achieved by clarifying the process of issuing Islamic sukuk in Malaysia based on identifying the responsible authority for issuing sukuk, and specifying the issuance requirements, as well as its guidelines and regulatory principles. In addition, it is necessary to consider in detail the types of Islamic sukuk issued in Malaysia in the period from 2001 to 2021. The most significant steps and incentives taken by the Malaysian government to expand the Malaysian Sukuk market are clarified in the study’s conclusion, in an effort to promote Malaysian investment in Islamic sukuk.